IMPLIKASI DINAMIKA DAN PENEGAKAN REGULASI ORGANISASI KEMASYARAKATAN (ORMAS) DI JAWA BARAT - Jauhari, Moh. Ahsanuddin; Nurhayani, Neng Yani; Najmudin, Nandang (Jurnal Hukum Media Justitia Nusantara, 2022)
This research aims to analyse the existence of Community Organisations (Ormas) which are part of supporting the acceleration of development in the life of the nation and state as well as their presence which has the potential to create new primordials that are prone to conflict. This research is included in the type of doctrinal research that is descriptive analytical. The results of this study conclude that, first: The regulation of Community Organisations (Ormas) must pay attention to its enforcement, so that the application of these rules is in accordance with the laws and regulations and does not give the impression of dictatorship, refressive and political (like and dislike). Second: The formulation of regulations on Community Organisations (Ormas) must really pay attention to community consensus on philosophical, sociological and juridical aspects, so that a common perception will be created that can work together in supporting the acceleration of the development of the life of the nation and state.